ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (STUDI KASUS PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI TAHUN 2014) - Poppy Indriani; Titan Terzagie (Profita, 2016)
This study to analyze the influence of company size, profitability of the Company, the Company Solvency, Auditor Opinion, Earning Per Share and Total Audit Committee Audit Delay either partially or simultaneously on the company LQ 45 listed in the Indonesia Stock Exchange in 2014. This study uses quantitative data in the form of financial statements are derived from website www.idx.co.id and www.sahamok.co.id, sampling technique used purposive sampling technique. Sample of 39 companies. Then, the data analysis technique used is descriptive statistics, classical assumption test and multiple linear regression analysis using SPSS program. The results showed that: (1) The size of the Company has no significant effect on Audit Delay, shown with sig 0.109> 0.05 (2) Profitability perusahaa no significant effect on Audit Delay, shown with sig 0.083> 0.05 ( 3) Solvency Company has no significant influence on Audit Delay, shown with sig 0.730> 0.05 (4) Opinion Auditor has no significant effect on the Audit Delay, indicated by the value 0.738> 0.05 (5) EPS has a significant influence the audit Delay, shown with sig 0.030 0.05 (7) Company Size, Profitability, Solvency, Auditor Opinion, EPS, and Total Audit Committee simultaneously affect the Audit Delay, shown with sig 0.005 <0.05.